Estimating Risks of Arrest and Criminal Populations: Regression Adjustments to Capture–Recapture Models. (December 2019) - Bouchard, Martin; Morselli, Carlo; Macdonald, Mitch; Gallupe, Owen; Zhang, Sheldon; Farabee, David
The size of criminal populations is unknown, and policy decisions are typically based only on the number of offenses and offenders that come to the attention of the criminal justice system. However, the size of criminal populations may follow different trends than what is observed in official data. We use a regression-adjusted capture–recapture model to estimate the number of people at risk of arrest for offenses involving amphetamine-type stimulants (ATS) from arrests and rearrests occurring in Quebec, Canada, controlling for year of first arrest, age, and gender. The 4, 989 individuals arrested were the visible part of an estimated 42, 541 [36, 936, 48, 145] individuals otherwise at risk of arrest (12%). Additional results show that trends in criminal populations and risks of arrest vary across offense type and drug classifications.